An Analysis of Students Writing Anxiety At IKIP PGRI Pontianak (Journal of English Language Teaching and Education (JELTE), 2022)
The emergence of anxiety in writing will affect the results of writing, the students are anxious how to use proper grammar, and they are worried if their writing will be evaluated. Several previous studies examined students in the early semester and found that their anxiety is still high, this study aimed to analyze writing anxiety to know the types and the levels of writing anxiety experienced by the students. This study involved sixth semester students of the English Education Study Program at IKIP PGRI Pontianak, with a total of 36 students, 25 of whom were female and 11 were male. The research method used is descriptive quantitative, where the data analysis statistically, and the data were collected through SLWAI questionnaire adapted from Cheng (2004). The result showed that students in the sixth semester still experienced writing anxiety even though it was at a moderate level with a percentage 53%, while the types of writing anxiety was measured based on three types: Cognitive Anxiety, Somatic Anxiety, and Avoidance Behavior, data analysis showed that students experienced Cognitive Anxiety with the highest mean score of 18.41 among the two types mentioned. The researcher hopes that this study will useful for readers that want to know about writing anxiety, and this research can be used as additional references for other researcher that has similar topic in the future.